Near Disappearance of Splenorrhaphy as an Operative Strategy for Splenic Preservation After Trauma. Issue 3 (March 2022) - Ko, Ara; Radding, Sydney; Feliciano, David V.; DuBose, Joseph J.; Kozar, Rosemary A.; Morrison, Jonathan; Kundi, Rishi; Maddox, John; Scalea, Thomas M.
Background: Splenorrhaphy was once used to achieve splenic preservation in up to 40% of splenic injuries. With increasing use of nonoperative management and angioembolization, operative therapy is less common and splenic injuries treated operatively are usually high grade. Patients are often unstable, making splenic salvage unwise. Modern surgeons may no longer possess the knowledge to perform splenorrhaphy. Methods: The records of adult trauma patients with splenic injuries from September 2014 to November 2018 at an urban level I trauma center were reviewed retrospectively. Data including American Association for the Surgery of Trauma splenic organ injury scale, type of intervention, splenorrhaphy technique, and need for delayed splenectomy were collected. This contemporary cohort (CC) was compared to a historical cohort (HC) of splenic injuries at a single center from 1980 to 1989 (Ann Surg 1990; 211: 369). Results: From 2014 to 2018, 717 adult patients had splenic injuries. Initial management included 157 (21.9%) emergent splenectomy, 158 (22.0%) angiogram ± embolization, 371 (51.7%) observation, and only 10 (1.4%) splenorrhaphy. The HC included a total of 553 splenic injuries, of which 313 (56.6%) underwent splenectomy, while splenorrhaphy was performed in 240 (43.4%). Those who underwent splenorrhaphy in each cohort (CC vs HC) were compared. Conclusion: The success rate of splenorrhaphy has not changed. However, splenorrhaphy now involves only electrocautery with topical hemostatic agents and is used primarily in low-grade injuries. Suture repair and partial splenectomy seem to be "lost arts" in modern trauma care.